Textile Prices in Early Byzantine Hagiographic Texts. Three Case Studies - Ireneusz Milewski (Studia Ceranea, 2020)
This text analyzes three early Byzantine source accounts on clothing prices from the beginning of the 5th to the early 7th centuries in Italy (Rome), Palestine (probably in Jerusalem), and Egypt (Alexandria). The compiled and discussed narrations were compared with other contemporary source reports, which feature analogical figures describing the amount of prices, wages, taxes, and other values or distances. By making a comparative analysis, the author came to the conclusion that these data are recurrent, and, therefore, unreliable. This observation also applies to the clothing prices discussed in the text, which, undoubtedly, should be considered topical.